2019
DOI: 10.1002/jms.4335
|View full text |Cite
|
Sign up to set email alerts
|

Combining MALDI‐2 and transmission geometry laser optics to achieve high sensitivity for ultra‐high spatial resolution surface analysis

Abstract: A transmission geometry optical configuration allows for smaller laser spot size to facilitate high‐resolution matrix‐assisted laser/desorption ionization (MALDI) mass spectrometry. This increase in spatial resolution (ie, smaller laser spot size) is often associated with a decrease in analyte signal. MALDI‐2 is a post‐ionization technique, which irradiates ions and neutrals generated in the initial MALDI plume with a second orthogonal laser pulse, and has been shown to improve sensitivity. Herein, we have mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 16 publications
1
53
0
1
Order By: Relevance
“…The Spectroglyph source has a MALDI-2 laser setup as described previously. 46 Briefly, the MALDI-2 laser (266 nm, FQSS266-200-STA, CryLaS GmbH, Berlin, Germany) is aligned parallel to the sample surface to irradiate the initial MALDI-1 plume at ~400 µm above the sample surface. A delay time was set to be 20 µs between the initial MALDI-1 event and the MALDI-2 laser irradiation.…”
Section: Instrument/acquisition Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…The Spectroglyph source has a MALDI-2 laser setup as described previously. 46 Briefly, the MALDI-2 laser (266 nm, FQSS266-200-STA, CryLaS GmbH, Berlin, Germany) is aligned parallel to the sample surface to irradiate the initial MALDI-1 plume at ~400 µm above the sample surface. A delay time was set to be 20 µs between the initial MALDI-1 event and the MALDI-2 laser irradiation.…”
Section: Instrument/acquisition Parametersmentioning
confidence: 99%
“…44 Early studies showed that a dramatic increase in signal could be produced with MALDI-2 while operating MALDI-1 energy at or below the ionization threshold,. 36,46 Here, we operated the MALDI-1 laser well above the ionization threshold to obtain maximum lipid signal without MALDI-2.…”
Section: Analysis Of Lipid Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, MALDI-2 has proven to improve sensitivity for certain molecular classes including liposoluble vitamins, monosaccharide and oligosaccharide, certain lipid classes, and exogenous drugs. 34,36,[38][39][40][41][42][43]45,46 Lipid classes that have been shown to have dramatically increased ion intensities in positive ion mode include hexosylceramides (HexCers), phosphatidylethanolamines (PEs), phosphatidylinositols (PIs), phosphatidylglycerols (PGs), phosphatidylserines (PSs), triacylglycerols (TGs), and cholesterol esters (CEs). 34 Interestingly, other classes of lipids such as phosphatidylcholines (PCs) were not shown to increase significantly with MALDI-2.…”
Section: Introductionmentioning
confidence: 99%
“…Although MALDI IMS is a rapidly developing field with dramatic improvements in instrument mass resolving power and scan speed introduced (Prentice et al, 2018;Spraggins et al, 2016), and the improvement of spatial resolution (Spivey et al, 2019), there are particular challenges for protein imaging (Heeren et al, 2009). Specifically, imaging and identification of low abundance and high molecular weight proteins is challenging (Ryan et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%